Productivity, cold hardiness and forage quality of spineless progeny of the Opuntia ficus indica 1281 x O. lindheimerii 1250 cross in Mendoza plain, Argentina - Guevara, Juan C.; Felker, Peter; Balzarini, Mónica G.; Páez, Sebastián A.; Estevez, Oscar R.; Paez, Marta N.; Antúnez, Juan C. (Journal of the Professional Association for Cactus Development, 2011)
The specialized photosynthetic system, Crassulacean Acid Metabolism (CAM) in cactus that provides several fold greater conversion of water to dry matter (DM) than grasses and broadleaf plants makes them especially suited for forage production in arid lands. Unfortunately the spineless fast growing Opuntia ficus?indica, that is widely used for forage in Brazil, North Africa and Mexico, is poorly adapted to regions outside the tropics due to lack of tolerance to freezing weather. To overcome this limitation, a wide interspecific cross was made between a fast growing, spineless, frost sensitive O. ficus?indica and spiny, cold tolerant, slow growing Texas native O. lindheimerii with the objective of combining the high productivity and spinelessness of the O. ficus?indica parent with the cold hardiness of the Texas native parent. The first part of this work compared 10 spineless progeny of this cross to the most cold hardy spineless forage species to date, i.e. O. ellisiana for forage production and crude protein (CP) content in Mendoza, Argentina (520 m elevation and 33º S latitude), where O. ficus?indica does not survive winters. Some of these progeny had 5 times greater productivity than O. ellisiana with equivalent cold tolerance. As previous Argentine Opuntia productivity trials were N limited, the responsiveness of these progeny to 3 rates of N fertilization was examined. It was found that N application stimulated about a 4 fold increases in dry biomass per plant compared to the treatment in which N was not added (12.7 and 3.2 kg DM plant?1, respectively) and an almost doubling in CP content of the 1?year?old cladodes (7.8 and 4.3% DM, respectively). None of the CP concentrations were high enough to meet the requirements of a 400?kg live weight lactating cow (10%), but the dose/N response did not appear to have reached a plateau. To determine the productivity per unit area, one trial with clone 42 was established. This clone produced a biomass of 40 t DM ha?1 in 4 years with a total of 625 mm rainfall. This is the greatest DM production recorded to date for such a low rainfall. This DM production corresponds to a carrying capacity of 0.76 Animal Unit (AU) ha?1. Future trials with the most productive and cold hardy of these spineless hybrid progeny, in combination with higher N fertilization levels that can meet lactating cow requirements are needed in additional test sites with more severe freezing weather regimes. Also, would be important to compare different ways to capture fertilizers such as to apply frequent, low application rates instead of an annual application as we done in the present study, taken into account the characteristics of the root mass of Opuntia. Other interesting alternative to prove for reducing the use of N?fertilizer could be to test if endophytic nitrogen?fixing bacteria such as Gluconacetobacter diazotrophicus fixes N with Opuntia.